Complex polypharmacy in bipolar disorder: Results from a real-world inpatient psychiatric unit. (December 2022) - Aguglia, Andrea; Natale, Antimo; Fusar-Poli, Laura; Amerio, Andrea; Costanza, Alessandra; Fesce, Fabio; Gnecco, Giovanni Battista; Marino, Margherita; Placenti, Valeria; Serafini, Gianluca; Aguglia, Eugenio; Amore, Mario
Highlights: About forty percent of patients affected by bipolar disorder received complex polypharmacy, defining as the assumption of ≥ 4 medications. Complex polypharmacy was associated with being single and unemployed, earlier age at onset, longer duration of illness, higher number of hospitalizations, a higher prevalence of medical and psychiatric comorbidity. Complex polypharmacy is also associated with the use of illicit substances, except for heroin. Need to develop clear guidelines for the long-term management of BD, implementing complementary psychosocial strategies to improve treatment adherence and outcomes. Abstract: Background: Multiple medications are frequently prescribed to patients with bipolar disorder (BD). The aim of the present study was to identify sociodemographic and clinical characteristics associated with complex polypharmacy in patients affected by BD. Methods: 556 patients with BD were included. A semi-structured interview was used to collect sociodemographic and clinical characteristics, as well as pharmacological treatment. Participants were divided in two groups, abased on the use of complex polypharmacy (i.e., a combination of 4 or more psychotropic medications). Differences between the two groups were evaluated with t-test and chi-squared test. A stepwise logistic regression was then applied to identify factors significantly associated with complex polypharmacy. Results: Patients with BD and complex polypharmacy were more likely to be single and unemployed. Moreover, earlier age at onset, longer duration of illness, higher number of hospitalizations, higher prevalence of medical and psychiatric comorbidity, and the use of illicit substances (except heroin) were associated with complex polypharmacy. In the logistic regression model, single status, older age, number of hospitalizations, and the presence of psychiatric comorbidities were regarded as factors significantly associated with complex polypharmacy. Conclusions: Our findings reflect the need to develop clear guidelines for the long-term management of BD, especially when pharmacological discontinuation is needed.